The Application of Critical Path Method (CPM) in Education Planning at Madrasah Ibtidaiyah - Fachruddin Azmi; Mesiono Mesiono; Uswatun Hasanah; Retno Pringadi (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to describe the application of the Critical Path Method (CPM) technique in educational planning at MIS Insan Kusuma Madani Namorambe Kapubaten Deli Serdang. This study uses a qualitative approach with a descriptive method, to explain the approach and method applied in the form of CPM techniques in educational planning. Obtaining data through observation techniques, interviews and document studies. The research data analysis technique uses data reduction (sorting), data presentation and conclusion drawing. Then, the data will be declared valid after being tested with data triangulation techniques, in the form of checking the data sources and data acquisition methods. The results of this study conclude that the empowerment of human resources (HR) and budget allocation for program financing at MIS Insan Kusuma implement CPM effectively as an effort to prioritize and schedule madrasa programs in a measurable and precise manner. Supporting this, the madrasah also collaborates with various elements of society in assisting education planning at MIS Insan Kusuma Madani Namorambe, starting from collaboration with non-governmental organizations (NGOs) and government institutions.